Waiver of a Right to Arbitrate by Resort to Litigation, in the Context of International Commercial Arbitration - Gillies, Peter; Dahdal, Andrew (Journal of International Commercial Law and Technology, 2007)
This paper examines the circumstances in which a party to an arbitration agreement may be deemed tohave waived its right to arbitrate a dispute comprehended by the agreement, by involvement in litigation concerning this dispute. The focus is on the law in common law jurisdictions, particularly Australia and theUnited States of America. United Kingdom law will also be briefly surveyed. The paper focuses on the 2006 decision of the Australian Federal Court in Comandate Marine Corp v Pan Australia Shipping Pty Ltd, whichafforded the topic significant treatment. The theoretical bases for sustaining waiver claims are analysed, includingwaiver as a discrete doctrine, abandonment, estoppel, election, repudiation of contract and variation of contract.The policies that underlie and inform the development of principles for testing waiver submissions are noted.

'Legal Traditions' and International Commercial Arbitration - Trakman, Leon (University of New South Wales, 2007)
Codes, laws and guidelines governing international commercial arbitration developed by such organizations as the International Court of Arbitration, the International Bar Association and the International Chamber of Commerce have been drafted against the background of Common Law and Civil Law values. In balancing these two great legal traditions, it was assumed that together they represent a composite legal tradition governing international commercial arbitration. The result of that assumption was decades of fine work enshrining international arbitration doctrines, principles, and rules of law and procedures that blend these two important legal traditions. More recent concerns have begun to raise such questions as: How pervasive are the Common and Civil Law traditions? Part I of this article asks: What is a legal tradition and how should it be distinguished from a legal culture in relation to international commercial arbitration? Part II reflects on the influence of legal culture on international commercial arbitration. Parts III, IV and V investigate the Common and Civil legal traditions in relation to national, regional and international commercial arbitration. Part VI evaluates the public traditions that surround international commercial arbitration. Part VII considers whether change in the traditions of international commercial arbitration represent culture change or culture shock. Part VIII emphasizes the value of building an inclusive international arbitration tradition. Part IX suggests ways in which international commercial arbitration can accommodate diffuse and changing local, regional and global influences upon it. Codes, laws and guidelines governing international commercial arbitration developed by such organizations as the International Court of Arbitration (ICA), the International Bar Association (IBA) and the International Chamber of Commerce (ICC) have been drafted against the background of Common Law and Civil Law values. In balancing these two great legal traditions, it was assumed that together they represent a composite legal tradition governing international commercial arbitration. The result of that assumption was decades of fine work enshrining international arbitration doctrines, principles, and rules of law and procedures that blend these two important legal traditions. From the doctrine of freedom of contract to specific rules of evidence and procedures that govern arbitral hearings, the international arbitration community has sought to maintain the respected legal traditions that lawyer-arbitrators and counsel find familiar and comfortable. More recent concerns, partly expressed by William K. Slate II, President of the American Arbitration Association, have begun to raise such questions as: How pervasive are the Common and Civil Law traditions? Are they sufficiently uniform in nature and operation to justify their dominant status in formulating codes, laws and rules governing international commercial arbitration? And has international commercial arbitration become unduly reliant upon both the Common and Civil Law traditions at the expense of other legal traditions that operate against the background of different and changing legal cultures? Part I of this article asks: What is a legal tradition and how should it be distinguished from a legal culture in relation to international commercial arbitration? Part II reflects on the influence of legal culture on international commercial arbitration. Parts III, IV and V investigate the Common and Civil legal traditions in relation to national, regional and international commercial arbitration. Part VI evaluates the public traditions that surround international commercial arbitration. Part VII considers whether change in the traditions of international commercial arbitration represent culture change or culture shock. Part VIII emphasizes the value of building an inclusive international arbitration tradition. Part IX suggests ways in which international commercial arbitration can accommodate diffuse and changing local, regional and global influences upon it.